Impact of a U.S. antismoking national media campaign on beliefs, cognitions and quit intentions - Duke, Jennifer C. (Health Educ Res, 2015)
In 2012, the Centers for Disease Control and Prevention launched a national tobacco education campaign, Tips From Former Smokers, that consisted of graphic, emotionally evocative, testimonial-style advertisements. This longitudinal study examines changes in beliefs, tobacco-related cognitions and intentions to quit smoking among U.S. adult smokers after a 12-week airing of the campaign (n=4040 adult smokers pre- and post-campaign). Exposure to the campaign was associated with greater odds of intending to quit within the next 30 days [odds ratio (OR)=1.28, P < 0.01] and within the next 6 months (OR=1.12, P < 0.05), and quit intentions were stronger among respondents with greater campaign exposure (OR=1.12, P < 0.01). Campaign exposure was also associated with significant changes in beliefs about smoking-related risks (ORs=1.15–2.40) and increased worries about health (b=0.30, P < 0.001). Based on study change rates applied to U.S. census data, an estimated 566 000 additional U.S. smokers reported their intention to quit smoking within the next 6 months as a result of viewing campaign advertisements. Campaign effects were consistent with the theory of reasoned action and an expanding body of research demonstrating that graphic, emotional advertisements are highly effective for prompting positive cessation-related cognitions and behavioral intentions.